Refractile bodies of Eimeria tenella are proteinaceous membrane-less organelles that undergo dynamic changes during infection - Burrell, Alana; Marugan-Hernandez, Virginia; Graefin Von Der Recke, Karolin; Aguiar-Martins, Kelsilandia; Gabriel, Heloisa Berti; Tomley, Fiona M.; Vaughan, Sue (Frontiers in Cellular and Infection Microbiology, 2023)
Introduction Refractile bodies (RB) are large membrane-less organelles (MLO) of unknown function found as a prominent mismatched pair within the sporozoite stages of all species of Eimeria, parasitic coccidian protozoa. Methods High resolution imaging methods including time-lapse live confocal microscopy and serial block face-scanning electron microscopy (SBF-SEM) were used to investigate the morphology of RB and other intracellular organelles before and after sporozoite invasion of host cells. Results Live cell imaging of MDBK cells infected with E. tenella sporozoites confirmed previous reports that RB reduce from two to one post-infection and showed that reduction in RB number occurs via merger of the anterior RB with the posterior RB, a process that lasts 20-40 seconds and takes place between 2- and 5-hours post-infection. Ultrastructural studies using SBF-SEM on whole individual sporozoites, both pre- and post-host cell invasion, confirmed the live cell imaging observations and showed also that changes to the overall sporozoite cell shape accompanied RB merger. Furthermore, the single RB post-merger was found to be larger in volume than the two RB pre-merger. Actin inhibitors were used to investigate a potential role for actin in RB merger, Cytochalasin D significantly inhibited both RB merger and the accompanying changes in sporozoite cell shape. Discussion MLOs in eukaryotic organisms are characterised by their lack of a membrane and ability to undergo liquid-liquid phase separation (LLPS) and fusion, usually in an actin-mediated fashion. Based on the changes in sporozoite cell shape observed at the time of RB merger together with a potential role for actin in this process, we propose that RB are classed as an MLO and recognised as one of the largest MLOs so far characterised.